Mortality reduction in relation to implantable cardioverter defibrillator programming in the Multicenter Automatic Defibrillator Implantation Trial-Reduce Inappropriate Therapy (MADIT-RIT) - Ruwald, Anne-Christine; Schuger, Claudio; Moss, Arthur J; Kutyifa, Valentina; Olshansky, Brian; Greenberg, Henry; Cannom, David S; Estes, N A Mark; Ruwald, Martin H; Huang, David T; Klein, Helmut; McNitt, Scott; et al. (Circulation. Arrhythmia and electrophysiology, 2014)
BACKGROUND: The benefit of novel implantable cardioverter defibrillator (ICD) programming in reducing inappropriate ICD therapy and mortality was demonstrated in Multicenter Automatic Defibrillator Implantation Trial-Reduce Inappropriate Therapy (MADIT-RIT). However, the cause of mortality reduction remains incompletely evaluated. We aimed to identify factors associated with mortality, with focus on ICD therapy and programming in the MADIT-RIT population. METHODS AND RESULTS: In MADIT-RIT, 1500 patients with a primary prophylactic indication for ICD or cardiac resynchronization therapy with defibrillator were randomized to 1 of 3 different ICD programming arms: conventional programming (ventricular tachycardia zone ≥170 beats per minute), high-rate programming (ventricular tachycardia zone ≥200 beats per minute), and delayed programming (60-second delay before therapy ≥170 beats per minute). Multivariate Cox models were used to assess the influence of time-dependent appropriate and inappropriate ICD therapy (shock and antitachycardia pacing) and randomized programming arm on all-cause mortality. During an average follow-up of 1.4±0.6 years, 71 of 1500 (5%) patients died: cardiac in 40 patients (56.3%), noncardiac in 23 patients (32.4%), and unknown in 8 patients (11.3%). Appropriate shocks (hazard ratio, 6.32; 95% confidence interval, 3.13-12.75; P<0.001) and inappropriate therapy (hazard ratio, 2.61; 95% confidence interval, 1.28-5.31; P=0.01) were significantly associated with an increased mortality risk. There was no evidence of increased mortality risk in patients who experienced appropriate antitachycardia pacing only (hazard ratio, 1.02; 95% confidence interval, 0.36-2.88; P=0.98). Randomization to conventional programming was identified as an independent predictor of death when compared with patients randomized to high-rate programming (hazard ratio, 2.0; 95% confidence interval, 1.06-3.71; P=0.03). CONCLUSIONS: In MADIT-RIT, appropriate shocks, inappropriate ICD therapy, and randomization to conventional ICD programming were independently associated with an increased mortality risk. Appropriate antitachycardia pacing was not related to an adverse outcome. CLINICAL TRIAL REGISTRATION URL: clinicaltrials.gov Unique identifier: NCT00947310.
Keywords: výsledek terapie; proporcionální rizikové modely; Chi-Square Distribution; Izrael; Prosthesis Failure; elektrická defibrilace; Male; Prosthesis Design; Japan; Risk Factors; protézy - design; Tachycardia, Ventricular; Kaplan-Meier Estimate; Kanada; Heart Rate; Proportional Hazards Models; Europe; rozdělení chí kvadrát; Kaplanův-Meierův odhad; Aged; mužské pohlaví; senioři; srdeční frekvence; Defibrillators, Implantable; Electric Countershock; Treatment Outcome; Evropa; Multivariate Analysis; Time Factors; senioři nad 80 let; Israel; lidé; United States; Humans; defibrilátory implantabilní; Japonsko; časové faktory; rizikové faktory; Aged, 80 and over; Spojené státy americké; Canada; selhání protézy; multivariační analýza; lidé středního věku; komorová tachykardie; Middle Aged